ACTIVITY TEST OF GUAVA (Psidium guajava L.) LEAF METHANOL EXTRACT AS CONTRACEPTION ANTIFERTILITY TO WHITE MICE (Rattus norvegicus) - Sri Retno Dwi Ariani; Endang Susilowati; Elfi Susanti VH; Setiyani Setiyani (Indonesian Journal of Chemistry, 2008)
The aim of this research is to know about if the guava (Psidium guajava L.) leaf methanol extract on 10.5 mg/mL and 21.0 mg/mL dossages indicate a positive test as contraception antifertility to white mice (Rattus norvegicus). The sample is guava leaf from Mungkid, Magelang Central of Java Indonesia. The animals experiment are the white mice on 140-300 g for female, 200-250 g for male and about 3 months of age in average. The steps of this research are : (1) preparing  sample, i.e. washing, drying on to indirect sunlight and make the sample into powder, (2) isolation the guava leaf powder in soxhlet instrument with hexane, (3) evaporation the sample with rotary evaporator until guava leaf hexane extract produced, (4) maseration the sample with methanol, (5) evaporation the sample with rotary evaporator until guava leaf methanol extract produced, (6) conducting contraception antifertility activity test to guave leaf methanol extract on 10.5 mg/mL and 21.0 mg/mL dossages to mice white. The results of this research are guava leaf methanol extract on 10.5 mg/mL and 21.0 mg/mL dossages indicate a negative contraception antifertility test to white mice but in these dossages have indicated that an antiimplantation effect (the total natality of fetus is less than the total implantation site in mice white).